Atomic Carbon Spraying: Direct Growth of Graphene on Customized 3D Surfaces of Ultrafast Optical Devices. Issue 12 (20th April 2020) - Uddin, Siam; Song, Yong‐Won
Abstract: Despite the long‐standing efforts to develop 3D graphene, which is critical for practical electronic, optoelectronic, and optical devices, the lack of synthetic methods and the use of conventional transfer approaches have limited its realization. Herein, a metal‐free, etching‐free, transfer‐free, direct synthesis of functional graphene is introduced that contours 3D‐structured surfaces of nonlinear optical devices, thereby maximizing the nonlinear interaction of graphene with guided light. Central to this method is the use of γ‐Al2 O3, a ceramic catalyst, which generates carbon atoms from the precursor molecules and supplies them for the graphene synthesis on the 3D structures located near the catalyst through spatial diffusion, described as atomic carbon spraying (ACS). The optical nonlinearity facilitated by ACS‐processed 3D graphene is experimentally verified by realizing both passively mode‐locked laser with a pulse width of 770 fs and ultrafast optical switching with 67% enhancement in nonlinear effect over 6 mm interaction length. Abstract : Atomic carbon spraying (ACS) is proposed for synthesizing functional graphene directly on arbitrary substrates contouring their 3D‐structured surfaces. This conformal growth of graphene guarantees a metal‐free, etching‐free, and transfer‐free process with ultimate graphene coverage on the optical devices maximizing nonlinear operation. Both femtosecond laser and ultrafast switching demonstrations verify the high nonlinearity of the ACS‐grown graphene.